Boganmeldelser - Bjarne Christensen; Jon Palle Buhl; Hans Klette; Hans-Gunnar Axberger; Britta Kyvsgaard; Kauko Aromaa; Vibeke Lund; Vagn Greve; Jacob Hilden Winsløw; Preben Freitag; Sysette Vinding Kruse; Henrik Stevnsborg; et al. (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews